Studi Penerapan Akuntansi Pesantren Pada Laporan Keuangan Yayasan Pondok Pesantren Tahfizh Bustanul Qur'an Melawi: Study of the Application of Islamic Boarding School Accounting in the Financial Reports of the Tahfizh Bustanul Qur'an Melawi Islamic Boarding School Foundation - Renaldi Renaldi; Muh. Sajjaj Sudirman (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2026)
The Tahfizh Islamic Boarding School Foundation, Bustanul Qur'an, receives income from student tuition fees, new student admissions, donations, alms, waqf, and donors. Therefore, it requires transparent and accountable financial reports as a form of financial management accountability to stakeholders. This research aims to analyze the application of the Islamic Boarding School Accounting Guidelines (PAP) in preparing the financial statements of the Tahfizh Bustanul Qur'an Islamic Boarding School in Melawi. This research uses a qualitative approach with a descriptive method. Primary data was obtained thru in-depth interviews with the pesantren treasurer, while secondary data consisted of cash books and transaction records from 2024. Data collection techniques included documentation, observation, and interviews, which were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The research results show that the financial statements of the Tahfizh Bustanul Qur'an Islamic boarding school are still very simple, only recording cash receipts and disbursements without following standard accounting cycles. The pesantren has not yet implemented the Pesantren Accounting Guidelines due to the limited understanding of financial managers regarding accounting standards and the absence of an accounting system that includes transaction analysis, journals, trial balances, adjustments, and financial statements. The implication of this research is the need for training for pesantren financial managers in implementing PAP and developing internal accounting policies that comply with SAK ETAP to improve the accountability and transparency of pesantren financial reporting.